Patterns and Mechanisms of Nutrient Resorption in Plants - Brant, Amber N.; Chen, Han Y.H. (Critical reviews in plant sciences, 2015)
Nutrient resorption (NR) plays a key role in the nutrient conservation of plants. However, a fundamental understanding of the mechanisms that control NR remains limited. In this review, we examine how intrinsic controls (e.g., genetic variability and plant development) and extrinsic environmental controls (e.g., climate and soil fertility) influence NR. We also examined conceptual NR advances, mass loss correction, measurement in non-leaf plant tissues for whole-plant nutrient budget accounting, and the use of stoichiometric ratios in place of individual elements. Nutrient resorption from senescing leaves is greater than that from stems/culms or roots. Nutrients resorbed from stems and roots in woody plants are lower than in non-woody plants. Deciduous plants are more efficient in resorbing leaf nutrients prior to senescence than are evergreen plants. Furthermore, reproductive efforts tend to increase NR. Along a latitudinal gradient of terrestrial biomes, nitrogen resorption efficiency decreases and phosphorus resorption efficiency increases with increasing temperature and precipitation; however, latitudinal patterns reflect the influences of several coupling factors such as genetic variation, climate, soil, and disturbance history. Nutrient fertilization experiments have demonstrated that increased soil fertility reduces NR. The inquiries into the impacts of ongoing climate change on NR are still at a nascent stage. Future NR studies are needed to better understand the independent effects of a wide range of genetic variation, plant development, and environment, and possibly the different responses of plants to environmental change; particularly elevated atmospheric CO 2 concentrations and global warming.